Review: Zaccarello, Michelangelo, ed. 2019. Textual Cultures: Texts, Contexts, Interpretation, 12.2 - D'Agostino, Giulia (Umanistica Digitale, 2021)
The volume Textual Cultures 12:2 contains some of the works presented at the fifth Incontro di Filologia Digitale (15-16 June 2018, Verona) with a foreword by Michelangelo Zaccarello. The theme of the event, “Born-digital editions and texts: theories, working approaches and methods”, aimed to provoke discussion on both shortcomings and breakthroughs in scholarly digital editing and to promote new projects. Moreover, the resulting collection of essays is defined by Zaccarello as an incentive to cooperation between Italian and North-American scholars. From the case studies gathered in this publication and the words of some contributors, it appears that an interesting matter of continuous debate among digital humanists and cause for reflection for readers is the dichotomy between the use of already established resources and workflows and the need to invent ad hoc tools and systems to answer new research questions. Since this incongruity can cause confusion in students and researchers entering the field and hinder the collaboration between different academic groups, the goal of my review is to address these problems from the perspective of an aspiring digital philologist in the hope of emphasising the conversations we still must have to ensure successful progress in these studies.